Pedagogical discourse in teaching reading comprehension in French - Quang, Nguyễn Việt (VNU Journal of Foreign Studies, 2013)
The article reseaches on pedagogical discourse of teachers in teaching reading comprehension. First of all, the author mentions the relationship between pedagogical discourse and roles of the teacher, then investigates the two activities, "reading" and "teaching to read" in order to highlight the point: "teaching reading is teaching how to read". The stages of a reading comprehension are also described in details on the basis of the three roles of the teacher. Finally, the paper presents results from a survey on the opinons of teachers about pedagogical discourse and comments on the four reading comprehension passages used by the Department of French Language and Culture, University of Languages and International Studies - VNU. These can be regarded as some of the suggestions in the field of methodology.